The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1002/(sici)1097-4547(20000501)60:3<328::aid-jnr7>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Photoreceptor phagocytosis selectively activates PPAR? expression in retinal pigment epithelial cells

Abstract: Phagocytosis of tips of rod outer segments (ROS) by retinal pigment epithelial (RPE) cells is vitally important for maintaining structural and functional integrity of the retina. We previously reported that receptor-mediated specific phagocytosis of ROS induces expression of early response genes coding for transcription factors. Here we study the expression of peroxisome proliferator-activated receptors (PPAR) -alpha, -delta (beta) and -gamma during ROS phagocytosis of rat RPE cells in primary cell culture, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 49 publications
(52 reference statements)
1
32
0
Order By: Relevance
“…Several lines of evidence suggest that OS phagocytosis is tightly coupled to RPE lipid and cholesterol metabolism: (i) Phagocytosis triggers expression of the AP-2 transcription factor (25), which regulates acid lipase expression (26); (ii) OS phagocytosis induces PPAR␥ (25), which increases transcription of cholesterol transporters (21); and (iii) selective metabolism of OS lipids by the RPE leads to the conservation and recycling of docosahexaenoic acid (27). In addition, RPE cells express several receptors and cholesterol transporters (28) that participate in lipoprotein uptake and cholesterol efflux.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that OS phagocytosis is tightly coupled to RPE lipid and cholesterol metabolism: (i) Phagocytosis triggers expression of the AP-2 transcription factor (25), which regulates acid lipase expression (26); (ii) OS phagocytosis induces PPAR␥ (25), which increases transcription of cholesterol transporters (21); and (iii) selective metabolism of OS lipids by the RPE leads to the conservation and recycling of docosahexaenoic acid (27). In addition, RPE cells express several receptors and cholesterol transporters (28) that participate in lipoprotein uptake and cholesterol efflux.…”
Section: Discussionmentioning
confidence: 99%
“…During starvation, an influx of fatty acids into the liver induces activation of PPAR (10), which, in turn, promotes ketogenesis through the up-regulation of Hmgcs2 expression; of genes involved in fatty acid transport, including acyl-CoA synthetase and fatty acid-binding protein; of genes involved in fatty acid metabolism peroxisomal acyl-coenzyme A oxidase and acyl-CoA dehydrogenase; and of genes involved in carnitine transport (carnitine palmitoyltransferase and organic cation/ carnitine transporter (OCTN2, encoded by SLC22A5)). The RPE expresses all three isoforms of PPARs (␣, ␦, and ␥), and PPAR-␥ expression was induced in RPE by phagocytosis of POS (11). These findings suggest that an influx of fatty acids into the RPE from POS phagocytosis can act as a signal for PPAR-mediated activation of fatty acid metabolism.…”
mentioning
confidence: 75%
“…In addition to intracellular metabolites, we also analyzed the Ringer's solution in the apical and basolateral compartments of these hfRPE for 13 C metabolites. We found that hfRPE cells incubated with [1][2][3][4][5][6][7][8][9][10][11][12][13] C]palmitate alone released significantly more (7-fold) labeled ␤-HB (75.2 Ϯ 49.7 pmol/cm 2 RPE in a 500-l volume over 3 h) into the apical chamber compared with the basal chamber (10.5 Ϯ 18.3 pmol/cm 2 RPE in a 1500-l volume over 3 h) (Fig. 3E).…”
Section: Resultsmentioning
confidence: 99%
“…phagocytosis of rod outer segments undergoing circadian shedding (35). Thus, the identification of SCD in RPE cells is quite interesting because it may play an important role in the process of complex lipid metabolism and trafficking in the RPE.…”
Section: Discussionmentioning
confidence: 99%